Chronotoxicity of Semen Strychni is associated with circadian metabolism and transport in mice. (14th December 2020) - Gao, Lu; Lin, Yanke; Wang, Shuai; Lin, Luomin; Lu, Danyi; Zhao, Yue; Xing, Huijie; Wu, Baojian
Abstract: Objectives: We aimed to determine the circadian responses of mice to Semen Strychni and to investigate the role of pharmacokinetics in generating chronotoxicity. Methods: Total extract of Semen Strychni was administered by oral gavage to wild-type (WT) and Bmal1 −/− (a circadian clock-deficient model) mice at different circadian time points for toxicity (including survival) and pharmacokinetic characterization. Nephrotoxicity and neurotoxicity were evaluated by measuring plasma creatinine and creatine kinase BB (CK-BB), respectively. Drug metabolism and transport assays were performed using liver/intestine microsomes and everted gut sacs, respectively. Key findings: Semen Strychni nephrotoxicity and neurotoxicity as well as animal survival displayed significant circadian rhythms (the highest level of toxicity was observed at ZT18 and the lowest level at ZT2 to ZT6). According to pharmacokinetic experiments, herb dosing at ZT18 generated higher plasma concentrations (and systemic exposure) of strychnine and brucine (two toxic constituents) compared with ZT6 dosing. This was accompanied by reduced formation of both dihydroxystrychnine and strychnine glucuronide (two strychnine metabolites) at ZT18. Bmal1 ablation sensitized mice to Semen Strychni- induced toxicity (with increased levels of plasma creatinine and CK-BB) and abolished the time dependency of toxicity. Metabolism of Semen Strychni (strychnine and brucine) in the liver and intestine microsomes of WT mice was more extensive at ZT6 than at ZT18. These time differences in hepatic and intestinal metabolism were lost in Bmal1 −/− mice. Additionally, the intestinal efflux transport of Semen Strychni (strychnine and brucine) was more extensive at ZT6 than ZT18 in WT mice. However, the time-varying transport difference was abolished in Bmal1 −/− mice. Conclusions: Circadian responses of mice to Semen Strychni are associated with time-varying efflux transport and metabolism regulated by the circadian clock (Bmal1). Our findings may have implications for optimizing phytotherapy with Semen Strychni via timed delivery.